Medikale Kulturen - Unterkircher, Alois (bricolage, 2008)
The fifth volume of "bricolage. Innsbrucker Zeitschrift für Europäische Ethnologie" analyzes health and disease-related concepts and practices of different social groups from a socio-historical and cultural-scientific point of view. Instead of the terminology of the older "folk medicine research", the authors orientate themselves on the concept of "medical culture(s)" as is the case in the identical research area "Cultural Encounters - Cultural Conflicts" of the University of Innsbruck. This association of humanities and social science subjects deals with different forms of cultural contact, whereby culture is understood as a dynamic system for the creation of meaning. So far, there is no anthology that does this with regard to specifically Austrian conditions and developments. The fifth volume of "bricolage" tries to fill this gap and would like to stimulate further discussion in this field of research in Austria.